2021
DOI: 10.1001/jamainternmed.2020.7570
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of SARS-CoV-2 RNA Test Results Among Patients Who Recovered From COVID-19 With Prior Negative Results

Abstract: The data are publicly available. Analysis code for replication is provided via the weblink in the main text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 5 publications
3
42
1
2
Order By: Relevance
“…However, the substantial number of infants who received iv antibiotics until the exclusion of bacterial co-infection justifies the increasing concern of a possible negative impact of the virus on antibiotic stewardship. Interestingly, in contrast to what has been reported for older children with COVID-19 [13], 5 infants had positive PCR for more than 3 weeks although with high Ct values which was suggestive that the virus was not transmissible [14].…”
Section: Table 1 Epidemiological and Clinical Characteristics Of Infacontrasting
confidence: 80%
“…However, the substantial number of infants who received iv antibiotics until the exclusion of bacterial co-infection justifies the increasing concern of a possible negative impact of the virus on antibiotic stewardship. Interestingly, in contrast to what has been reported for older children with COVID-19 [13], 5 infants had positive PCR for more than 3 weeks although with high Ct values which was suggestive that the virus was not transmissible [14].…”
Section: Table 1 Epidemiological and Clinical Characteristics Of Infacontrasting
confidence: 80%
“…This absence of the full-spectrum of COVID-19-related complications in this study is likely multifactorial. First, many of the COVID patients likely recovered from previous COVID or had only mild infection, which is supported by our low rates of COVID-19-related symptoms and imaging findings [22,23]. Second, the low ISS scores in our study indicate that a large portion of our COVID cohort sustained minor trauma which perhaps is not a powerful enough insult to trigger COVID-19 complications.…”
Section: Discussionsupporting
confidence: 58%
“…Recent studies showed Ag-RDT is unable to detect SARS-CoV-2 at a Ct value of more than 19 [ 22 ]. Other reports have revealed the diagnostic sensitivity of Ag-RDT to be 95% at Ct values < 25 but declines drastically to 20–40% when the Ct value is > 25 [ 23 ]. In contrast to all these observations, the GenBody TM COVID-19 Ag test COVAG025 showed diagnostic sensitivities of 90–100% at Ct levels ≤ 25 in residual samples and unconfirmed fresh samples, which also further persisted at Ct levels > 25.…”
Section: Discussionmentioning
confidence: 99%